Simulation based complex energy assessment of office building fenestration - Motuzienė, Violeta; Juodis, Egidijus Saulius (Journal of Civil Engineering and Management, 2010)
The number of office buildings with highly fenestrated facades is currently increasing in Lithuania and neighboring countries. Highly fenestrated facades reduce energy consumption for lighting and simultaneously increase energy consumption for heating, cooling, air conveying and may cause thermal and visual discomfort. Pursuing to reduce negative effects of the highly glazed facade, special glasses are frequently used. However, such windows usually increase demand for lighting energy. Therefore, when making early decisions about glazing the building, it is important to have a complex evaluation of energy demand related to the specific case. The paper presents the results of analysis made using energy simulation tools. The obtained results have shown that when shading is not applied, the north is the most energy efficient orientation to glazing for an air conditioned office building in cool climate zones like Lithuania. The most energy efficient window‐to‐wall ratios (WWR) for the south, east and west oriented façade are 20%, whereas for the north it makes 20–40%. However, such WWR values do not satisfy standard requirements for day lighting.